Hegel: the reconciliation of spirit in disgrace - Másmela, Carlos (Estudios de Filosofía, 1994)
The idea of the Phenomenology of Spirit is intimately linked to the idea of system. But the conception of the latter is part of Hegel's philosophic itinerary, wherefore it is by no means easy to understand the link existing between the two. It is considered, as an example, that the Phenomenology is an introduction to the system, or its first part. The present article pretends to interpret it as an introduction; however, not in the sense of a preliminary essay that would be external to the system, but rather as a presupposition for its constitution. This effort supposes that the idea of the Phenomenology is approached from within its structure and its internal unfolding. The idea is thereby revealed in the phenomenon of disgrace. Although Hegel attributes it at first to the conscience of self as the end of its history, neither does the phenomenon mentioned end in it, nor does it find its origin there. This origin is to be found in the absolute reconciliation of spirit. The reconciliation of absolute spirit in disgrace determines the intention of the Phenomenology and constitutes the condition that makes the conception of the system